A Comprehensive Study on Physical Properties of Antiperovskite GeNCa3 - Selgin Al; Ahmet İyigör (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
A comprehensive study has beencarried out in order to reveal physical properties of antiperovskite compoundGeNCa3 in the cubic structure. This study presents extensiveproperties including mechanical, electronic, vibrational and thermodynamical bymeans of generalised approximation approach within the density functionaltheory. The equilibrium lattice constant and bulk modulus of the compound areobtained via energy-volume data. The mechanical stability evaluation isconducted based on Born’s criteria using elastic constants. Subsequently,electronic band structures and partial and total densities of states are computedfor antiperovskite GeNCa3. The electronic band structure of thecompound reveals a metallic character with highest contribution to theconductivity Ge 4p and Ca 3d states. Moreover, phonon distribution curve is obtainedby employing the linear response technique. The results indicate a dynamicallystable compound. Finally, thermodynamic properties such as entropy and specificheat value and the results are presented.